Garment proposal for elderly individuals with reduced mobility (ModaPalavra e-periódico, 2025)
Design for specific needs requires customized anthropometric studies that consider the end user, connecting to physical ergonomics, which involves the study of adapting the environment to the individual, encompassing aspects of comfort, effort, well-being, and motor activity. This study aims to report on a proposal for the design of a garment adapted for individuals with reduced mobility, linking the phenomenon of social inclusion with inclusive design and fashion. To develop the paper, a literature review was conducted on inclusive fashion, with a particular focus on artifacts for motor-related deficiencies. A case study was carried out with a user from this group. The design methodology used was the Inclusive Design Toolkit from the Engineering Design Centre (2017). To develop the proposal, sketches representing the garment to be manufactured were designed using software, with the aid of digital modeling. According to the user’s feedback, the garment did not restrict her range of motion, allowing for greater mobility of the upper limbs and making it easier to put on and take off. Understanding the user’s routine activities and needs regarding the clothing object—from the immaterial style to the tangible and textile choice—was essential to delivering a result tailored to her specific needs and preferences. The thermal properties of the fabric and the wearability pleased the user; however, medium-term testing is necessary.
Keywords: Inclusive fashion; Inclusive design; Reduced mobility; Ergonomy